Complete expiratory central airway collapse at general anesthesia recovery: a case report - Jie Lyu; Jiamin Miao; Jihong Zhu; Gang Chen (Journal of International Medical Research)
Expiratory central airway collapse is a degenerative tracheobronchial disease that is often overlooked because of its nonspecific clinical features. A man was admitted for evaluation of tracheal nodules. Following bronchoscopic biopsy, a significant increase in airway pressure occurred during anesthesia recovery. Laryngospasm was suspected, and tracheal intubation was performed. Bronchoscopy revealed an almost completely collapsed tracheal lumen. A Y-shaped silicone stent was placed using a rigid bronchoscope to support the airway, allowing spontaneous ventilation to resume. A retrospective review of the images suggested a diagnosis of excessive dynamic airway collapse. The silicone stent was removed after 2 weeks because of discomfort, and no subsequent dyspnea was observed. This case highlights that excessive dynamic airway collapse is easily missed. Anesthesiologists must be educated on this condition, maintain a thorough understanding of the patient’s state and illness, and have emergency airway equipment readily available to restore ventilation promptly in cases of severe airway collapse.